ANALISIS PERTIMBANGAN HUKUM PENGADILAN AGAMA PENETAPAN NOMOR 92/Pdt.P/2023/PA.Ptk TENTANG PERMOHONAN ASAL USUL ANAK - NIM. A1011191321, SYARIFAH FAIRUS (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract . The application for the origin of the child was granted by the Religious Court based on Article 42 and Article 2 paragraph 1 of Law Number 1 of 1974, which states that a legitimate child is a child born from a valid marriage according to religious law. As long as the applicant can prove the existence of a valid marriage, the child will be recognized as a legitimate child with full legal status. However, if the marriage cannot be proven, the application is still granted, but the child is only recognized as a biological child, which means that the relationship is only established with the mother and her mother's family. This determination provides legal certainty for children, especially in terms of identity and civil rights.The formulation of the problem in this study is